2019
DOI: 10.1634/theoncologist.2018-0536
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of a Tailored Cognitive-Behavioral Therapy Mobile Application for Anxiety in Patients with Incurable Cancer

Abstract: Background The aim of this study was to test the efficacy of a tailored cognitive‐behavioral therapy (CBT) mobile application (app) to treat anxiety in patients with incurable cancer. Materials and Methods Patients with incurable cancers (n = 145) who reported elevated anxiety symptoms at two cancer centers were randomized to receive either the CBT mobile app for anxiety or a mobile health education program (control) delivered via tablet computers, which patients self‐administered over 12 weeks. To assess anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(142 citation statements)
references
References 45 publications
6
126
0
5
Order By: Relevance
“… ( Cheong et al, 2018 ) South Korea Colorectal cancer 102 / 41% women/ 58 ± 12 years Pre-post Wearable device and application that included rehabilitation exercise program and information on their disease and treatment None 12 weeks EORTC-C30 74% Improved EORTC symptoms of fatigue and nausea/vomiting. ( Park et al, 2019 ) Republic of Korea Lung cancer 90 / 54% women / 55.1 ± 8.7 years Pre-post App delivered physical rehabilitation program (Smart Aftercare app) None 12 weeks EORTC QLQ-C30 90% Improved role, emotional and social functioning, fatigue, appetite, diarrhea ( Trinh et al, 2018 ) Canada Prostate cancer 46 / all men / 73.2 ± 7.3 years Pre-post Accelerometer, wrist-worn activity tracker and Web based application None 12 weeks FACT-General 91% Improved emotional well-being ( Lozano-Lozano et al, 2019 ) Spain Breast cancer (Overweight/obese) 80 / all women / age 59 ± 9 years Pre-post Healthy eating and physical activity feedback app (BENECA) None 8 weeks EORT QLQ-C30 73% Improved global health, physical, emotional, social and cognitive functioning, fatigue, dyspnea, insomnia Cognitive behavioral therapy / behavioral change (6 studies) ( Greer et al, 2019 ) USA …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… ( Cheong et al, 2018 ) South Korea Colorectal cancer 102 / 41% women/ 58 ± 12 years Pre-post Wearable device and application that included rehabilitation exercise program and information on their disease and treatment None 12 weeks EORTC-C30 74% Improved EORTC symptoms of fatigue and nausea/vomiting. ( Park et al, 2019 ) Republic of Korea Lung cancer 90 / 54% women / 55.1 ± 8.7 years Pre-post App delivered physical rehabilitation program (Smart Aftercare app) None 12 weeks EORTC QLQ-C30 90% Improved role, emotional and social functioning, fatigue, appetite, diarrhea ( Trinh et al, 2018 ) Canada Prostate cancer 46 / all men / 73.2 ± 7.3 years Pre-post Accelerometer, wrist-worn activity tracker and Web based application None 12 weeks FACT-General 91% Improved emotional well-being ( Lozano-Lozano et al, 2019 ) Spain Breast cancer (Overweight/obese) 80 / all women / age 59 ± 9 years Pre-post Healthy eating and physical activity feedback app (BENECA) None 8 weeks EORT QLQ-C30 73% Improved global health, physical, emotional, social and cognitive functioning, fatigue, dyspnea, insomnia Cognitive behavioral therapy / behavioral change (6 studies) ( Greer et al, 2019 ) USA …”
Section: Resultsmentioning
confidence: 99%
“…We identified 17 RCTs ( Willems et al, 2017 ; Mendoza et al, 2017 ; Graetz et al, 2018 ; Ferrante et al, 2018 ; Admiraal et al, 2017 ; Compen et al, 2018 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Greer et al, 2019 ; Ham et al, 2019 ; Ji et al, 2019 ; Kubo et al, 2019 ; Rosen et al, 2018 ; Uhm et al, 2017 ; Urech et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2018 ) and 8 pre-post design studies ( Børøsund et al, 2019 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; McCarroll et al, 2015 ; Pappot et al, 2019 ; Park et al, 2019 ; Pope et al, 2019 ; Trinh et al, 2018 ). Nine studies (5 RCTs and 4 pre-post designs) tested physical activity / rehab / fitness interventions ( Mendoza et al, 2017 ; Frensham et al, 2018 ; Galiano-Castillo et al, 2016 ; Ji et al, 2019 ; Uhm et al, 2017 ; Cheong et al, 2018 ; Lozano-Lozano et al, 2019 ; Park et al, 2019 ; Trinh et al, 2018 ), six studies – CBT interventions (4 RCTs and 2 pre-post designs) ( McCarthy et al, 2018 ; Willems et al, 2017 ; Compen et al, 2018 ; Greer et al, 2019 ; Greer et al, 2019 ; Ham et al, 2019 ; Børøsund et al, 2019 ), three studies - mindfulness/stress management interventions (3 RCTs) ( Kubo et al, 2019 ; Rosen et al, 2018 ; Urech et al, 2018 ), two studies - social support (1 RCT and 1 pre-post design) ( Zhu et al, 2018 ; Pappot et al, 2019 ), two studies - information/psychoeducation (2 RCTs) ( Graetz et al, 2018 ; Admiraal et al, 2017 ), two studies – weight management (1 RCT and 1 pre-post design) ( Ferrante et al, 2018 ;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there was potentially little room for improvement on this outcome. In fact, a recent study by Greer et al found that cancer patients who had the highest levels of distress at study entry benefited most from a mobile psychosocial application. It is possible that My Guide might be more beneficial for women experiencing poorer levels of health‐related quality of life, and this possibility should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The Hospital Anxiety and Depression Scale will be used to evaluate changes in anxiety and depression by using two 7-item Depression and Anxiety sub-scales. (65). The reliability and validity has been shown to be acceptable in individuals with prostate cancer (66).…”
Section: Health Outcomesmentioning
confidence: 99%